S100A4 expression is associated with poor prognosis in patients with resectable gastrointestinal stromal tumor. Issue 1 (1st January 2019) - Shen, Wenlong; Tan, Xiaojie; Hao, Fengyun
ABSTRACT: S100A4 is particularly associated with the progression and metastasis of numerous human malignancies. This study was designed to examine the clinicopathologic significance of S100A4 in gastrointestinal stromal tumor (GISTs). The level of OPNS100A4 expression in a large cohort of resectable GISTs was evaluated with immunohistochemistry. Its correlation with the clinicopathologic parameters of patients with resectable GISTs was analyzed. A survival analysis was performed to evaluate the prognostic significance of S100A4 expression using Kaplan-Meier method. Results: In 108 patients with resectable GISTs, the most high-risk GISTs had a strong level of S100A4 expression. Strong S100A4 expression was significantly associated with tumor size, mitosis, and recurrence, but not gender and age. Patients with weak S100A4 expression had a relatively longer disease-free survival compared to patients with strong S100A4 expression.Therefore, S100A4 expression is a putative marker for tumor progression and an adverse prognosis in GISTs.